1996
DOI: 10.1097/00004647-199601000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Measurement of Salicylate Hydroxylation and Glutamate Release in the Penumbral Cortex following Transient Middle Cerebral Artery Occlusion in Rats

Abstract: Using the microdialysis technique and laser-Doppler flowmetry, we performed simultaneous measurement of salicylate hydroxylation and glutamate release along with local CBF in the ischemic penumbral cortex of rat brain subjected to normothermic transient middle cerebral artery (MCA) occlusion. Cortical CBF fell to 24 +/- 11% (mean +/- SD) during ischemia and recovered to 84 +/- 16% during reperfusion. Extracellular glutamate levels increased by 6.5-fold above baseline 10 min following MCA occlusion but subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(73 citation statements)
references
References 54 publications
5
66
2
Order By: Relevance
“…The general time course observed in the control and tamoxifen groups (ie, an initial peak followed by a gradual reduction), is consistent with the decreases seen previously in the penumbra, 19,20 and is different from the pattern observed in more complete ischemia where EAA levels generally rise throughout the ischemic period, and to a much higher level. 2,21 Although the magnitude and time course of EAA concentrations in the current study are similar to what others have found in penumbra defined by moderate blood flow reductions, 19,22 other investigators in penumbra defined by electrical characteristics found small, transient, or even no changes in EAA levels.…”
Section: Eaa Release Via Glt-1 Transporter Reversalsupporting
confidence: 83%
“…The general time course observed in the control and tamoxifen groups (ie, an initial peak followed by a gradual reduction), is consistent with the decreases seen previously in the penumbra, 19,20 and is different from the pattern observed in more complete ischemia where EAA levels generally rise throughout the ischemic period, and to a much higher level. 2,21 Although the magnitude and time course of EAA concentrations in the current study are similar to what others have found in penumbra defined by moderate blood flow reductions, 19,22 other investigators in penumbra defined by electrical characteristics found small, transient, or even no changes in EAA levels.…”
Section: Eaa Release Via Glt-1 Transporter Reversalsupporting
confidence: 83%
“…However, these changes are much less severe in the ischemic penumbra (Lipton, 1999). Extracellular glutamate concentrations in penumbral tissue are elevated to a lesser extent than in the core (Wang et al, 2001), estimated at 30-50 µM in different studies (Shimada et al, 1990;Wahl et al, 1994;Morimoto et al, 1996).…”
Section: Stroke: Causes Neuronal Injury and Increased Glutamate And Cmentioning
confidence: 98%
“…However, after daily repetition of stimulations, after discharges increase in duration, eventually progressing to spontaneous seizure activity. Blockade of the NMDA receptor inhibits kindling epileptogenesis, demonstrating the necessity of NMDA receptor activation (Croucher et al, 1988(Croucher et al, , 1992Morimoto et al, 1996).…”
Section: In Vitro Models-in Vitro Models Of Se Have Also Been Developmentioning
confidence: 99%
“…Cerebral cortex contains the major part of ischemic penumbra, in which cells are still only mildly damaged and may undergo apoptosis rather than necrosis (26). Therefore, cerebral cortex could be salvageable after ischemic events (17,28). In experimental models of focal brain ischemia infused with edaravone for 90 min its major oxidation product (2-oxo-3-(phenylbutazono)-butanoic acid, OPB) was found in the penumbra area.…”
Section: H Yoshida Et Almentioning
confidence: 99%